IMPROVING QUALITY OF EDUCATION THROUGH ASSESSMENT TEACHER CLASS PERFORMANCE - Nurismilida Nurismilida (Universitas Negeri Medan, 2017)
Abstract : Improving the Quality of Educators Through Classroom Teacher Performance Assessment. Implementation of teacher performance appraisal is intended not only to realize professional teachers, as it can show appropriately about the activities of teachers in the classroom, and help them to improve their knowledge and skills. So as to contribute directly to improving the quality of learning undertaken, while assisting teacher career development as a professional. To ensure that every teacher is a professional in his field, teacher performance appraisal should be conducted for teachers in all formal education units organized by government, local government and community. Teacher performance assessment results can be utilized to develop teacher performance profiles as inputs in the preparation of the Sustainable Food Development program. Keywords: Improvement, Teacher Competency, Master Performance Performance. Abstrak : Peningkatan Mutu Pendidik Melalui Penilaian Kinerja Guru Kelas. Pelaksanaan penilaian kinerja guru dimaksudkan bukan hanya untuk mewujudkan guru yang profesional, karena dapat menunjukkan secara tepat tentang kegiatan guru di dalam kelas, dan membantu mereka untuk meningkatkan pengetahuan dan keterampilannya.Sehingga berkontribusi secara langsung pada peningkatan kualitas pembelajaran yang dilakukan, sekaligus membantu pengembangan karir guru sebagai tenaga profesional.Untuk meyakinkan bahwa setiap guru adalah seorang profesional di bidangnya, maka penilaian kinerja guru harus dilakukan terhadap guru di semua satuan pendidikan formal yang diselenggarakan oleh pemerintah, pemerintah daerah, dan masyarakat.Hasil penilaian kinerja guru dapat dimanfaatkan untuk menyusun profil kinerja guru sebagai input dalam penyusunan program Pengembangan Keprofesian Berkelanjutan. Kata Kunci : Peningkatan, Kompetensi Guru, Penilian Kinerja Guru